Challenges and Opportunities of Family Leisure Organization for Younger School-Age Children: Parents’ Opinions - Ručinskė, Deimantė; Bilbokaitė-Skiauterienė, Ieva; Širiakovienė, Asta (Jaunųjų mokslininkų darbai, 2021)
The success of education in the family depends on the time spent by the parents with the child, the varied and meaningful leisure time. However, in Lithuania little attention is paid to the fact that the working hours and holiday time of parents raising school-age children are coordinated with the children’s school schedule . The lack of  occupation for children  usually poses many social problems. The organization and content of family leisure depends on the ability to involve children in a variety of activities according to their interests and needs. Properly organized leisure distracts children from spending time meaninglessly, harmful habits, provides an opportunity to develop various skills, to communicate with family members. Meaningful family leisure time is often limited by certain obstacles: family composition, age of children, financial situation, parents’ work schedule, supply of entertainment, etc.The aim of this research was to find out the problems and possibilities of organizing leisure time for younger school children in the family. Responding to the goal,  it was sought to answer the questions: how is the leisure time of younger school-age children organized in the family, and what problems do parents face? In order to achieve the aim of the research and to collect the research data, a written questionnaire survey of parents was used.An empirical study conducted in October 2019 (N = 90) showed that family leisure is always or often planned by parents, usually taking into account the financial situation of the family. Families choose both active and passive activities that do not require prior preparation. It turned out that one of the most important problems in planning family leisure time is the insufficient supply of events for families with younger school-age children. There is a lack of events that promote active leisure.
Keywords: leisure time organization; family leisure time; parents of younger school-age children